PDE4B Is a Homeostatic Regulator of Cyclic AMP in Dendritic Cells - Chinn, Amy M.; Salmerón, Cristina; Lee, Jihyung; Sriram, Krishna; Raz, Eyal; Insel, Paul A. (Frontiers in Pharmacology, 2022)
Chronic decreases in the second messenger cyclic AMP (cAMP) occur in numerous settings, but how cells compensate for such decreases is unknown. We have used a unique system – murine dendritic cells (DCs) with a DC-selective depletion of the heterotrimeric GTP binding protein Gas – to address this issue. These mice spontaneously develop Th2-allergic asthma and their DCs have persistently lower cAMP levels. We found that phosphodiesterase 4B (PDE4B) is the primary PDE expressed in DCs and that its expression is preferentially decreased in Gas-depleted DCs. PDE4B expression is dynamic, falling and rising in a protein kinase A-dependent manner with decreased and increased cAMP concentrations, respectively. Treatment of DCs that drive enhanced Th2 immunity with a PDE4B inhibitor ameliorated DC-induced helper T cell response. We conclude that PDE4B is a homeostatic regulator of cellular cAMP concentrations in DCs and may be a target for treating Th2-allergic asthma and other settings with low cellular cAMP concentrations.